Towards multi-agency violence prevention and victim support. An investigation of police-accident and emergency service liaison - Shepherd, Jonathan (The British journal of criminology, 1998)
Since many serious violent offences are not reported, effective police-accident and emergency department (AED) joint working is important in increasing the chances of offenders being brought to justice and increasing access to victim support services. The research was driven by hypotheses that detection is hindered by poor liaison; that the roles of AED personnel are confused; that treatment of injured victims is not based on an ethical framework to protect their interests or the interests of society; and that there is insufficient time in the AED to address criminal justice and other issues as well as treating physical injuries. Liaison was investigated by means of triangzdated methods comprising surveys of random stratified samples of police officers and AED personnel and a case series of victims treated in five large AEDs. It was found that there was almost no knowledge of existing formal guidance among health and police practitioners who actually deal with victims. Most of the injured were transported from bars and the street to the AED where, for long periods, they became trapped in a medical environment dominated, to the exclusion of all else, by the need to treat physical injuries. This, in effect, prevented them from reporting offences. Efforts to preserve confidentiality, far from protecting the interests of patients and society, meant that AED health professionals ignored the circumstances and psychological impact of injury and risk of further injury. This meant that the roles of other agencies were not considered. This very narrow focus was at odds with the instincts of most health professionals, half of whom believed they should have some role in victim protection and support, the detection of crime and community crime prevention. The results of this study suggest that, based on the exercise of victim choice, there are extensive opportunities ethically to improve rates of detection and access to victim support